PROJECTION ON FICTIONAL CHARACTERS AS AN EMOTIONAL CATALYST - Rujina, Valeria (E-Journal VFU, 2024)
An analysis using the methodology of critical psychology regarding the emotional connection between people and fictional characters. A deeper look into the ancient tradition of human art and storytelling through the lens of social psychology. Comparison between modern approaches towards creating characters and their perception and the approaches of the past. Analysis of the way stories influence society and the way society influences stories. Personal growth via imagination and entertainment